Thermal decomposition behavior of tobacco stem Part II: Kinetic analysis - POLAT, SEVGİ (TAYLOR & FRANCIS INC, 2016)
As a continuation of the previous study on the thermal degradation behavior of tobacco stem, this work is focused on the kinetics of pyrolytic decomposition. Thermogravimetric analysis of tobacco stem samples was conducted under nitrogen atmosphere at different heating rates of 5, 10, 15, and 20 degrees C/min at a temperature range of 25-1,000 degrees C. The kinetic parameters, such as activation energy, pre-exponential factor, and reaction order, were determined by applying the Coats-Redfern method for the main pyrolysis occurred in the second zone by means of the decomposition of hemicellulose, cellulose, and lignin at a temperature range 180-540 degrees C. In addition, the activation energy was calculated using various degradation models, including Kissinger, Friedman (FR), Flynn-Wall-Ozawa (FWO), and Kissinger-Akahira-Sunose (KAS). The average activation energy of tobacco stem was calculated to be 150.40, 230.76, 216.97, and 218.56 kJ/mol by the Kissinger, FR, FWO, and KAS models, respectively.
Keywords: Biomass; kinetics; pyrolysis; TGA; tobacco stem; PYROLYSIS